IMPLEMENTASI PADA ALAT BUKTI JEJAK DIGITAL DALAM PENEGAKAN HUKUM TINDAK PIDANA PENIPUAN ONLINE - Muhammad Safei; Sandra Dewi; Olivia Anggie Johar (Collegium Studiosum Journal, 2025)
The rapid development of information technology has led to an increase in online fraud crimes that utilize electronic media and internet networks. In enforcing the law against such crimes, digital trace evidence plays a crucial role in uncovering criminal acts, identifying perpetrators, and proving guilt before the court. However, the implementation of digital evidence in law enforcement practices still faces various challenges, including legal, technical, and human resource aspects. This study aims to analyze the implementation of digital trace evidence in the law enforcement of online fraud crimes within the jurisdiction of the Riau Regional Police. The research employs a socio-legal method with statutory and case approaches. Data were collected through literature studies and supporting interviews, and analyzed using qualitative descriptive analysis. The findings indicate that digital trace evidence has been significantly utilized in the processes of investigation, prosecution, and judicial proof of online fraud cases. Nevertheless, its effectiveness is constrained by limited digital forensic facilities, the complexity of electronic evidence examination, and the lack of public awareness regarding reporting mechanisms and the preservation of digital evidence. Therefore, strengthening regulations, enhancing law enforcement capacity, and increasing public legal awareness are essential to achieve effective, fair, and legally certain law enforcement.